THE ANALYSIS OF NURSING STUDENT SOFT SKILLS DEVELOPMENT BETWEEN LECTURE AND PROBLEM BASED LEARNING APPROACHES 2011 - Hilman Syarif (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction: Student Centered Learning (SCL) is an effective method to develop student's soft skills and hard skills which are very important to support their successful carrier later. This research was conducted to identify the differences of developed soft skills between students who learn with PBL method and lecturing method. Methods: Descriptive comparative method was used in this study. The samples consisted of 15 students who learned with PBL method and 15 students who learned with lecturing method. The sample for this research was selected by random sampling method. Results: The result showed that the average of student's soft skills score in PBL method was 122.63, while student's soft skills score in lecturing method was 116.27. Discussion & Conclusion: There was significant difference of student's soft skills in PBL method and lecturing method (p value = 0.038; α = 0.05). This study recommends nursing program management, faculty of medicine at the University of Syiah Kuala keeps PBL method running and develops other methods which facilitate hard skills and soft skills are development. Keywords: nursing students, soft skill, PBL